ETHNOLINGUISTIC STUDY OF ENGLISH AND UZBEK PROVERBS: PROVERBS ABOUT CLOTHING - Maxsumov Rustam Maxamadiyevich (The Conference Hub, 2025)
This thesis presents a comprehensive ethnolinguistic analysis of clothing-related proverbs in English and Uzbek languages, examining how these linguistic expressions encode cultural knowledge, values, and worldviews. The study employs a mixed-methods approach, combining quantitative corpus analysis with qualitative ethnographic investigation to explore the relationship between language and culture as manifested in proverbial wisdom. The research corpus consists of 150 clothing-related proverbs (75 English, 75 Uzbek) collected from traditional sources, literary works, and contemporary usage. Through systematic thematic analysis, the study identifies five major categories: social status and hierarchy, moral and ethical teachings, practical wisdom and economy, identity and authenticity, and appearance versus reality. The analysis reveals both universal human concerns about clothing and appearance, as well as culture-specific interpretations that reflect distinct historical experiences, religious influences, and social structures.
Keywords: ethnolinguistics, proverbs, comparative linguistics, cultural semantics, English, Uzbek, clothing symbolism, cross-cultural analysis